Answer:
y = 0
Step-by-step explanation:
It is always a good idea to look at the question and make some observations about it. Here, you might observe ...
- all of the bases are powers of 3: 243 = 3^5; 9 = 3^2
- y is a factor of every exponent
The latter observation is important, because it means that when y=0, every exponential expression has a value of 1. Hence y = 0 is a solution.
__
To solve the equation, you can write it in terms of powers of 3.
(3^5)^(-y) = (3^-5)^(3y)·(3^2)^(-2y)
3^(-5y) = 3^(-15y)·3^(-4y)
3^(-5y) = 3^(-19y)
-5y = -19y . . . . . . . . equating exponents; equivalent to taking log base 3
14y = 0 . . . . . . . . . . add 19y
y = 0 . . . . . . . . . . . one solution
______
The rules of exponents we used are ...
(a^b)(a^c) = a^(b+c)
(a^b)^c = a^(bc)
1/a^b = a^-b
the two triangles are congruent
Answer:
Angle 1 = 80 (by definition)
Angle 3 = 180 - 80 = 100
Angle 4 + Angle 2 = 90
Also, Angle 2 = 40 (by definition)
So Anglee 4 = 50
False. A reflection over the y-axis would result in: (-8,5)
Answer:
y = 3/4 + 7
Step-by-step explanation:
you must put the equation into the form of y = mx + b
add 6x to both sides and put it in front of the 56
8y = 6x + 56
y must be by itself by x does not so we divide everything by 8
y = 6/8x + 7
we must simplify the fraction 6/8
y = 3/4x + 7